Efectos de la Ractopamina sobre los parámetros zootécnicos del pollo de engorde - Remolina Rivera, Diego; Cortez Machado, Luz; Latorre Ramirez, Sergio (Spei Domus, 2007)
The purpose of this paper is to fi nd the effects produced by the inclusion of the Ractopamine in the zootecnic parameters. This product belongs to the family of the Fenetano-lamines, group that due to its chemical structure has the power to unite and to active the receptors that are found, in a cellular level, at different tissues of the production animals. The Ractopamine has been studied and it has been proved its effect in different production animal species. It is also known as an agent of repartition, because it redirects the nutrients that were not used and are going to be stored such as lipids again, to generate more lean meat. Th is quality allows us to state that besides optimizing the animal productive performance, it will improve the final product characteristics. Then, it was decided to give the first stepand prove the effects of Ractopamine in the zootecnic parameters of broiler. A population of 24.960 Cobb female was taken, that was divided in 2 groups in the same conditions. As this product is just included in the production fi nal phases until the 22nd day of production, it was determined that in the 2nd group, for having a lower level of corporal weight, Ractopamine were included in the ration, with one dose of 5ppm and supplement of 1% of Lysine. The measurement of the zootecnic parameters took place 2 times per week since day 0, but for the analysis, just the ones that were obtained before the inclusion of the Ractopamine in the diet, were taken into account. The “Essay” group, by its side, had the difference of weight gain between measurements with a value of 0,65 g; mortality 0.061% and effi ciency with a positive and significant difference of 0,55%,  no one of these indexes reaches an significant statistic difference, with a 90% of reliability. Although the obtained results are not conclusive, there’s not any statistics support that prove them; but the results are interesting and show an attractive behavior of the Ractopamine. Taking into account that the dose and protocol used were experimental, more tests should be made with a different dose, times of inclusion and % of supplementation with lysine, for knowing thereal potential of the Ractopamine, using other genetic lines, too.